Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1038/labinvest.3700415
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of CpG islands of p16 associated with progression of primary gastric carcinomas

Abstract: Inactivation of p16 by methylation of CpG islands is a frequent early event in gastric carcinogenesis. The positive relationship between p16 methylation and the clinical characteristics of gastric carcinomas (GC) has not been reported to date. In the present study, a DHPLC assay to quantify p16 methylation was established (detection limit by fluorescence detector: 1:255 (Methlyated vs Unmethylated)). The proportion of methylated p16 in the representative samples was confirmed and standardized by clone sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 28 publications
(39 reference statements)
3
53
0
1
Order By: Relevance
“…Although the quantitative MethyLight results in both initial biopsy and follow-up rebiopsy samples were consistent with those of the methylation-specific PCRdenatured high performance of liquid chromatography assay in the present study, we did not observe a significant increase of oral cancer risk in patients with oral epithelial dysplasia with the strong p16 methylation by MethyLight. Unlike in cultured cell lines, we reported that methylation status of CpG sites within the p16 CpG island in human tissue samples was not always homogeneous (17). Thus, different primer sets used in two kinds of assays might be the main reason accounting for detection difference of p16 methylation in these oral epithelial dysplasias.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the quantitative MethyLight results in both initial biopsy and follow-up rebiopsy samples were consistent with those of the methylation-specific PCRdenatured high performance of liquid chromatography assay in the present study, we did not observe a significant increase of oral cancer risk in patients with oral epithelial dysplasia with the strong p16 methylation by MethyLight. Unlike in cultured cell lines, we reported that methylation status of CpG sites within the p16 CpG island in human tissue samples was not always homogeneous (17). Thus, different primer sets used in two kinds of assays might be the main reason accounting for detection difference of p16 methylation in these oral epithelial dysplasias.…”
Section: Discussionmentioning
confidence: 88%
“…S1; 150 bp for methylated copy and 151 bp for unmethylated copy) and analyzed using denatured high performance of liquid chromatography at Peking University School of Oncology. Paraffin blocks of xenografted p16-methylated RKO and p16-unmethylated MGC803 human cancer cell lines were used as positive and negative control for each experiment throughout the analysis procedure (including DNA extraction, bisulfite modification, methylation-specific PCR, and denatured high performance of liquid chromatography detection), respectively (17).…”
Section: Methodsmentioning
confidence: 99%
“…The methylation status of p16 CpG island was detected by the 150/151-bp methylation-specific PCR (MSP), 392-bp denatured high-performance liquid chromatography (DHPLC), or clone sequencing as described (Herman et al, 1996;Luo et al, 2006). In brief, the bisulfite-modified genomic DNA was amplified using the methylated/unmethylated p16-specific primer sets in the MSP assay or using the CpG-free universal primer set in the DHPLC and sequencing assays (Supplementary Table 4S).…”
Section: Analysis Of P16 Methylationmentioning
confidence: 99%
“…Because the crucial CpG sites are not characterized for most CpG island-containing genes, we used the DHPLC assay to validate alterations of the methylation status of all 90 genes. DHPLC is a convenient assay for quantifying the proportion of methylated CpG islands we established previously [33,34]. Like bisulfite sequencing, PCR products (400-1000 bp) of methylated and unmethylated CpG islands amplified with CpG-free primers are analyzed with this assay.…”
Section: Alterations Of Dna Methylation As Biomarkers For Metastasis mentioning
confidence: 99%